A pediatric approach to management of skin growths in basal cell nevus syndrome. Issue 3 (17th February 2020) - Fisher, Jonathan; Moustafa, Danna; Su, Katherine A.; Bartenstein, Diana W.; Lilly, Evelyn; Kroshinsky, Daniela; Hawryluk, Elena B.
Abstract: Little guidance on management of basal cell nevus syndrome in children exists. We report a case series of four patients diagnosed with BCNS in early childhood, in whom several highly suspicious lesions were biopsied, but several smaller and questionably concerning lesions were treated with therapies that are more tolerable for children, including topical imiquimod, 5‐fluorouracil, cryotherapy, or touch electrodessication following topical anesthetic cream. These therapies were well tolerated, and all residual or persistent lesions were subsequently biopsied and found to be benign. This approach is often preferable for pediatric BCNS patients, in whom concerning lesions can be identified clinically and managed compassionately. However, any lesion that exhibits growth, bleeding, or symptoms should be biopsied for definitive diagnosis.